Associations between milking technology, herd size and milk production parameters on commercial dairy cattle farms - Ivanyos, Dorottya (Array, 2020)
The aim of the study was to survey the milking technology and to analyse the associations between milking parlour type, herd size, and milk production parameters on dairy cattle farms. The milking technology was surveyed by using a questionnaire in 417 Hungarian dairy herds with 177,514 cows in 2017, and it was compared with their official farm milk production data. The surveyed farms were categorized according to their size (1-50, 51-300, 301-600, and >600 cows) and to their milking parlour types (herringbone, parallel, carousel, and others). The relationships were analysed by multivariate linear models, one-way ANOVA, and Fisher’s exact test. Pairwise comparisons were performed by Tukey’s post hoc tests. The prevailing type of milking parlour was herringbone (71.0 %), but on larger farms the occurrence of parallel and carousel parlours increased (p<0.001). The number of milking stalls per farm increased with herd size (p<0.001). Farms with herringbone parlour had significantly smaller number of milking stalls than that of parallel (p=0.022) and carousel (p<0.001) parlours, and the cows were mostly milked two times, while in carousel milking parlours mostly three times a day. As the herd size increased, so did daily milk yield (p<0.001) and daily milk production per cow (p<0.001). Herd size was associated with somatic cell count (p<0.001). The type of milking parlour showed significant association with daily milk yield (p=0.039) and dairy units with herringbone milking system had the lowest milk quality. Our findings show that herd size has greater impact on milk production parameters than milking technologies.